Factor Affecting Evidence Based Maternity Care Practice among Nurses in a Tertiary Hospital - Subedi, Shova; Niraula, Hira Kumari; Subedi, Bhusan Kumara (Nepal Journal of Health Sciences, 2025)
Introduction: As the largest group of healthcare professionals, nurses have crucial role for delivering evidence based practice for positive maternity outcomes along with cost effective quality care. The personal and organizational context influences its implementation.Objective: To find out the factor affecting evidence based maternity care practice among nurses in a Tertiary Maternity hospital.Method: Descriptive cross sectional study was done with sample of 84 nurses. Data were collected by using self-administered questionnaires which include attitude scale as well as barrier and facilitator scales. SPSS was used for data analysis.Result: Almost all nurses (97.6%) provided their opinion that evidence based practice is beneficial for the positive patient outcomes and professional development. Majority nurses (78.6%) believed that the care they delivered was evidence based. The nurses demonstrated a positive attitude toward evidence-based practice, with mean score of 2.45 + 0.41. However, they reported experiencing barriers to implementing evidence based practice in their daily clinical practice. Overall barrier scale had a mean score of 2.38 + 0.47, with the organizational subscale identified as the most significant barrier, scoring 2.14 + 0.55. Most important facilitating factor felt by the respondents were ‘Emphasized evidence based practice in nursing curriculum of all level’ (82%); ‘Reward and motivation for evidence based practice’ (79.8%) and ‘Adequate staffing and team work culture’ (79.7%).Conclusion: Emphasizing evidence based practice among nurses, the supporting factors should be enhanced and overcome identified barriers. As a result, the professional development of the nurses is also achieved along with positive health outcomes